Three new species of Australian anthiadine fishes, with comments on the monophyly of Pseudanthias Bleeker (Teleostei: Serranidae) - Gill, Anthony C.; Pogonoski, John J.; Johnson, Jeffrey W.; Tea, Yi-Kai (Zootaxa, 2021)
Three new species of anthiadine species are described from specimens trawled from Australian waters. Pseudanthias paralourgus n. sp. is described from five specimens collected off southeastern Queensland. It resembles P. elongatus (Franz, 1910) from Japan to the South China Sea, but differs in male live coloration. The remaining two species are assigned to the genus Tosana Smith & Pope, 1906, which is newly diagnosed to include the two new species and the type species from southern Japan to the South China Sea, T. niwae Smith & Pope, 1906. The two new species, T. dampieriensis n. sp. described from three specimens from off Western Australia and T. longipinnis n. sp. described from 42 specimens from off eastern Australia, differ from each other and from T. niwae in various meristic and morphometric details. Pseudanthias paralourgus co-occurs with T. longipinnis. Molecular phylogenetic analysis of mitochondrial COI yielded a tree with the three Tosana species forming the sister group of a clade consisting of P. paralourgus n. sp., P. elongatus and the type species of Pseudanthias Bleeker, 1871, P. pleurotaenia (Bleeker, 1857). Our preliminary phylogenetic analyses suggest that Pseudanthias comprises a polyphyletic assemblage of species that also includes Nemanthias Smith, 1954, Luzonichthys Herre, 1936, Tosanoides Kamohara, 1953, Odontanthias Bleeker, 1873, and Serranocirrhitus Watanabe, 1949, thus highlighting the need for a revised generic classification of species currently assigned to Pseudanthias.